The legacy of the Group Areas Act and the possible consequences of the repeal of the Act - Keyser, Heidi(Heidi-Marie) (Stellenbosch : Stellenbosch University, 2012)
Study Project (M. in Town and Regional Planning) -- University of Stellenbosch, 1991.